Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1016/j.cardiores.2005.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial proteases and matrix remodeling in inflammatory heart disease

Abstract: Recently, it has been demonstrated that myocardial inflammation plays a pivotal role in the development and progression of congestive heart failure. The myocardial inflammatory reaction not only affects myocardial hypertrophy and apoptosis, but it has a major influence on the regulation of extracellular matrix turnover. The balance between collagen synthesis and degradation is of crucial relevance in maintaining the structural integrity of the heart. Therefore, the overwhelming inflammatory response, as seen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 109 publications
2
71
0
2
Order By: Relevance
“…Alteration in the matrix degradation system caused by inflammatory mediators, oxygen species, and neurohumoral reactions leads to an impairment of LV function as observed in myocarditis and inflammatory cardiomyopathy. 23 The imbalance of the matrix-degrading system with induced expressions of MMPs and plasminogen activators as well as the reduced expressions of tissue inhibitors of MMPs leads to a pathologic collagen turnover, with the loss of structural integrity of the heart and an impairment of LV function. 23 Interestingly, we could observe an increase in myocardial mRNA levels of MMP-2 and -9 in rats with DCM ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alteration in the matrix degradation system caused by inflammatory mediators, oxygen species, and neurohumoral reactions leads to an impairment of LV function as observed in myocarditis and inflammatory cardiomyopathy. 23 The imbalance of the matrix-degrading system with induced expressions of MMPs and plasminogen activators as well as the reduced expressions of tissue inhibitors of MMPs leads to a pathologic collagen turnover, with the loss of structural integrity of the heart and an impairment of LV function. 23 Interestingly, we could observe an increase in myocardial mRNA levels of MMP-2 and -9 in rats with DCM ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…23 The imbalance of the matrix-degrading system with induced expressions of MMPs and plasminogen activators as well as the reduced expressions of tissue inhibitors of MMPs leads to a pathologic collagen turnover, with the loss of structural integrity of the heart and an impairment of LV function. 23 Interestingly, we could observe an increase in myocardial mRNA levels of MMP-2 and -9 in rats with DCM ( Figure 5). It is reported that AT 1 R may be involved in the development of cardiac hypertrophy by increasing ECM ±dP/dt, rate of intra-ventricular pressure rise and decline; EAM, experimental autoimmune myocarditis; EF, ejection fraction; FS, fractional shortening; group N, aged-matched untreated rats; group T10, rats with heart failure treated with telmisartan (10 mg kg -1 day -1 ); group V, rats with heart failure treated with vehicle; HR, heart rate; HW, heart weight; HW/BW, ratio of heart weight to body weight; LVDd, left ventricular dimension in diastole; LVDs, left ventricular dimension in systole; LVEDP, left ventricular end-diastolic pressure; LVP, left ventricular pressure; MBP, mean blood pressure; n, no.…”
Section: Discussionmentioning
confidence: 99%
“…Thus a heterogeneous pattern of ECM remodeling occurs in ischemic DCM where enhanced ECM accumulation and degradation occur simultaneously. In cases of infectious DCM, the robust inflammatory response within the myocardium heralds the induction of cytokine and growth factor receptor pathways which can augment ECM synthesis and accumulation (71,221,228,325,372). Using a selective corrosive technique which reveals the collagen skeletal framework amenable for scanning electron microscopy, Rossi (368) demonstrated that significant ECM remodeling occurred in patients with DCM secondary to Chagastic myocarditis (221).…”
Section: Myocardial Remodeling In Cardiomyopathic Diseasementioning
confidence: 99%
“…26,37 Altered MMP expression and activation can lead to an imbalance between collagen synthesis/degradation in the myocardial ECM 37,38 and a change in the structural integrity of the heart. 26,39 In the adult heart, the role of MMPs is associated with repair and protection in response to pathological injury 39 ; while in the immature heart, MMPs play an essential role in tissue remodeling and cell migration. 27 Growth of the fetal heart occurs by both hyperplasia and hypertrophy of cardiomyocytes 40 and structural integrity of the myocardium is regulated by the complex balance of synthesis/degradation of ECM components such as fibrillar collagens.…”
Section: Role Of Mmps In Cardiac Remodelingmentioning
confidence: 99%
“…25,26 Both the inflammatory response and oxidative stress have been shown to favor the activation of MMPs as well as regulating gene transcription in heart tissue. 26,27 Metalloproteinases are important enzymes that contribute to cardiac remodeling.…”
Section: Introductionmentioning
confidence: 99%